Community based participatory research as a promising practice for addressing vaccine hesitancy, rebuilding trust and addressing health disparities among racial and ethnic minority communities - Sophie E. O’Bryan; Fatima Muñoz; David Smith; Adriana Bearse; Blanca Melendrez; Biren Kamdar; Cynthia James-Price; Daniel Ramirez; Argentina E. Servin (Human Vaccines & Immunotherapeutics, 2024)
ABSTRACTThe COVID-19 pandemic disproportionately affected racial and ethnic minority communities across the United States (U.S.). Despite the disproportionate burden of COVID-19 faced by communities of color, Black and Hispanic communities are less likely to be fully vaccinated than White non-Hispanic Persons. Health inequity and vaccine hesitancy are complex phenomena that require multilevel responses tailored to the unique needs of each community, a process that inherently necessitates a high level of community engagement in order to develop the most effective health interventions. Building on the principles of community based participatory research (CBPR) and with the support of the National Institutes of Health (NIH), Project 2VIDA! was born. A multidisciplinary collaborative of academic researchers, community members, and clinicians whose aim is to foster sustainable partnerships to reduce the burden of COVID-19 in Hispanic and Black communities across Southern California. Our model was designed to meet our community members where they were – whether on their lunch break or picking their children from school. This CBPR model has been well received by community members. Future health interventions focused on reducing health disparities should prioritize the role of the community, leverage the voices of key community partners, and be grounded in equitable power sharing.